Clinical Utility of SCALE-B to Predict Hepatitis B Virus Relapse, Hepatitis B Surface Antigen Loss After Antiviral Cessation in Asian Patients After 2-Year Follow-up - Kaewdech, Apichat; Assawasuwannakit, Suraphon; Sripongpun, Pimsiri; Chamroonkul, Naichaya; Tangkijvanich, Pisit; Piratvisuth, Teerha (Frontiers in Medicine, 2022)
Background Discontinuation of antiviral therapy in chronic hepatitis B (CHB) patients leads to a higher HBsAg loss; yet clinical relapse (CR) may occur. SCALE-B score was developed to predict off-treatment CR; however, validation of SCALE-B beyond a 48-week follow-up is rare. We studied whether SCALE-B and HBV RNA could predict outcomes in CHB patients after a 2-year follow-up. Methods Ninety-two Thai CHB patients who stopped antiviral treatment were followed up; baseline characteristics, qHBsAg, HBcrAg, and HBV RNA were collected at the time of discontinuation, and SCALE-B scores were calculated. Patients were followed up every 12 weeks for 48-week, then the intervals were upon primary doctors. Follow-up data regarding virological relapse (VR), CR, and HBsAg loss were obtained. Results The median follow-up duration was 142 weeks; the cumulative incidences of VR, CR, and HBsAg loss were 65.2%, 33.7%, and 7.6%, respectively. After 48-week, VR and CR plateaued, but HBsAg loss increased from 2.2% to 7.6%. According to the SCALE-B strata, VR, CR, and HBsAg loss were significantly different. The highest stratum (>320) was associated with higher VR, CR and lesser HBsAg loss when compared with the lowest stratum, with adjusted hazard ratios of 5.0 (95%CIs: 1.8–14.4), 10.44 (95%CIs: 1.4–79.1), and 0.04 (95%CIs: 0.004–0.43), respectively. Conclusions At a median follow-up of 2.5 years after discontinuing therapy, HBsAg loss in Thai patients was found to increase over time. SCALE-B is a valuable tool for predicting CR, VR, and HBsAg loss; HBV RNA is not significantly associated with long-term outcomes.